2006
DOI: 10.1111/j.1553-2712.2006.tb01737.x
|View full text |Cite
|
Sign up to set email alerts
|

The Verbal Numeric Pain Scale: Effects of Patient Education on Self-reports of Pain

Abstract: Background: Emergency department (ED) patients are frequently asked to provide a self-report of the level of pain experienced using a verbal numeric rating scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…According to the use or not of the WHO's Analgesic Ladder, in compliance with the indication for referred pain intensity, patients were divided, respectively, in groups A and B. Scale used to evaluate pain intensity by nurses was the Verbal Numeric Scale (VNS) 11 . Demographic and clinical data, and already mentioned variables of interest were collected by in Excel program.…”
Section: Methodsmentioning
confidence: 99%
“…According to the use or not of the WHO's Analgesic Ladder, in compliance with the indication for referred pain intensity, patients were divided, respectively, in groups A and B. Scale used to evaluate pain intensity by nurses was the Verbal Numeric Scale (VNS) 11 . Demographic and clinical data, and already mentioned variables of interest were collected by in Excel program.…”
Section: Methodsmentioning
confidence: 99%
“…One study of acute pain in the emergency department showed no differences between a printed brochure and a video in terms of impact on participants’ self-rated pain, and no differential effects by educational level. 8 Another study of decision making about analgesia for labor and childbirth pain among women in the latter stages of pregnancy showed no differences between a booklet-style and an audio-guided decision aid, and no differential effects by years of education. 39 The present findings therefore show how health education principles developed in the context of a range of other health conditions can also be applied to promote self-management of chronic joint pain.…”
Section: Discussionmentioning
confidence: 98%
“… 38 Many previous evaluations of health education interventions have examined subgroups based on educational level. 8 , 15 , 39 Literacy and health literacy are complex constructs 40 and although simplified assessment methods are available, even the simplest require individual assessments, 41 whereas level of education may be a more straightforward and cost-effective criterion for targeting interventions, especially for those designed to be delivered to large groups or sections of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При оцінці нейропатичного болю найзручнішою в повсякденній медичній практиці є шкала нейропатичного болю (ШНБ; Neuropathic Pain Scale -NPS), розроблена вченими з Вашингтонського медичного університету B.S. Galer і M. Jensen в 1997 році [13,14]. У цій шкалі відображені специфічні якості болю (колючий, тупий, пекучий, холодний, ниючий, сверблячий) та глибина болю (глибокий чи поверхневий).…”
unclassified